Brief review on recent technology in particle image velocimetry studies on hemodynamics in carotid artery - A. Fahmi Huwaidi, M. Noor; Nasrul Hadi, Johari (Springer Science and Business Media Deutschland GmbH, 2022)
Cardiovascular disease is number one causes of morbidity and mortality in global. In-vitro studies are widely applied in the investigation of blood flow under pathological conditions to diagnose atherosclerosis in carotid arteries. In this manuscript, a brief review on the latest published articles was con ducted according to Preferred Reporting Items for Systematic Reviews and Me ta-Analyses on the particle image velocimetry (PIV) studies of blood flow in carotid artery geometries. Fourteen (14) recent articles on PIV from 2016 to 2020 in Scopus, PubMed and ScienceDirect databases were included. The data of the published articles were focused on the technical aspects of PIV flow measurement and were organized in two categories i.e. carotid phantom geometries constructions and the blood mimicking flow circuits. This systematic re view paper summarises the updated methodology in the PIV and identify potential areas to elucidate the accuracy and limitations of each method.